Theoretical-methodological reflections on some dilemmas in the study of clandestine sexual practices - Esparza Escalante, Miguel Angel; Yuni, José Alberto; Urbano, Claudio Ariel (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2020)
The article addresses some dilemmatic questions of a theoretical-methodological nature that arose in the exercise of reflexivity typical of all critically oriented social research. The study of clandestine social practices has historically attracted the interest of researchers for its methodological and ethical implications, the clandestine practices that we address refer to male sexuality, which adds another density to the research, especially in relation to fieldwork and the interpretation of information. In the first part, the text contextualizes the research that originates this reflection in conceptual terms and locates it in a specific socio-cultural space. Subsequently, some methodological decisions that structure our approach to fieldwork from the ethnographic approach are explained. In the last part, some methodological prescriptions of researchers in the field of sexuality studies and recognized authors of the ethnographic approach are contrasted, with records extracted from the field survey log, elaborated in the participant observation process carried out in clandestine sexual practices of men who have sex with men. This contrast aims to show the methodological tensions that the social researcher must face when dealing with an object connoted by clandestinity, as well as some dilemmatic questions of an ethical nature.